Resident evil. Welcome to Raccoon City [videorecording (Blu-Ray)] - Roberts, Johannes; Scodelario, Kaya, 1992-; John-Kamen, Hannah, 1989-; Amell, Robbie, 1988-; Hopper, Tom, 1985-; Jogia, Avan, 1992-; Logue, Donal, 1966-; McDonough, Neal; Alexandre, Maxime, 1971-; Korven, Mark (Sony Pictures Home Entertainment, 2022)
Set in 1998, this origin story explores the secrets of the mysterious Spencer Mansion and the ill-fated Raccoon City.